Rare co-occurrence of a Mullerian cyst and a Gartner's duct cyst - Purandare, Tanushree; Junnare, Ketaki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Vaginal cysts of embryological origin are a relatively rare entity. They are often small, solitary and asymptomatic, found incidentally on pelvic examination or imaging. Mullerian cysts are formed by remnants of paramesonephric (Mullerian) ducts, while Gartner's duct cysts are formed by remnants of mesonephric ducts (Wolffian) ducts. These are usually managed expectantly unless they become large and symptomatic. In this case, surgical excision is done. We report the case of a 36-year-old female who presented to the outpatient department of gynaecology with symptoms of mass per vaginum, vaginal discharge and pelvic pain. She did not have any bladder or bowel complaints. Upon pelvic examination, she was found to have a second degree uterovaginal prolapse with a decubitus ulcer and a reducible cystocele. The ulcer had a small opening giving continuous discharge. We suspected this to be a ruptured cyst along the right antero lateral vaginal wall. The patient was admitted for a cyst excision and vaginal hysterectomy. Only intraoperatively, another cyst along the posterior vaginal wall, close to the vault, was discovered. Histopathological examination confirmed the anterolateral one was a Mullerian cyst, unusually accompanied by a Gartner's duct cyst on the posterior vaginal wall.